Sulforaphane Protects Against Ethanol-Induced Apoptosis in Human Neural Crest Cells Through Diminishing Ethanol-Induced Hypermethylation at the Promoters of the Genes Encoding the Inhibitor of Apoptosis Proteins - Li, Yihong; Fan, Huadong; Yuan, Fuqiang; Lu, Lanhai; Liu, Jie; Feng, Wenke; Zhang, Huang-Ge; Chen, Shao-Yu (Frontiers in Cell and Developmental Biology, 2021)
The neural crest cell (NCC) is a multipotent progenitor cell population that is sensitive to ethanol and is implicated in the Fetal Alcohol Spectrum Disorders (FASD). Studies have shown that sulforaphane (SFN) can prevent ethanol-induced apoptosis in NCCs. This study aims to investigate whether ethanol exposure can induce apoptosis in human NCCs (hNCCs) through epigenetically suppressing the expression of anti-apoptotic genes and whether SFN can restore the expression of anti-apoptotic genes and prevent apoptosis in ethanol-exposed hNCCs. We found that ethanol exposure resulted in a significant increase in the expression of DNMT3a and the activity of DNMTs. SFN treatment diminished the ethanol-induced upregulation of DNMT3a and dramatically reduced the activity of DNMTs in ethanol-exposed hNCCs. We also found that ethanol exposure induced hypermethylation at the promoter regions of two inhibitor of apoptosis proteins (IAP), NAIP and XIAP, in hNCCs, which were prevented by co-treatment with SFN. SFN treatment also significantly diminished ethanol-induced downregulation of NAIP and XIAP in hNCCs. The knockdown of DNMT3a significantly enhanced the effects of SFN on preventing the ethanol-induced repression of NAIP and XIAP and apoptosis in hNCCs. These results demonstrate that SFN can prevent ethanol-induced apoptosis in hNCCs by preventing ethanol-induced hypermethylation at the promoter regions of the genes encoding the IAP proteins and diminishing ethanol-induced repression of NAIP and XIAP through modulating DNMT3a expression and DNMT activity.